2021
DOI: 10.3389/fpsyg.2020.606180
|View full text |Cite
|
Sign up to set email alerts
|

Uses and Perceptions of Music in Times of COVID-19: A Spanish Population Survey

Abstract: Since March 14, 2020, Spanish citizens have been confined to their homes due to the impact of the COVID-19 pandemic. Participating in musical activities has been associated with reduced anxiety and increased subjective wellbeing. The aim of this study is to analyze how Spanish citizens used music during the lockdown period. We also study perceptions of the impact music has in everyday life, in particular examining the respondents’ insights into the effects of listening to music in situations of isolation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
115
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(124 citation statements)
references
References 77 publications
8
115
0
1
Order By: Relevance
“…Results showed that caregivers tended to engage more frequently in music-related activities (e.g., listening to music) during social distancing compared with a typical day before social restrictions. This finding agrees with a general trend revealed by studies showing an increase in the time adults spent on musical activities during the COVID-19 pandemic (Cabedo-Mas et al, 2020;Krause et al, 2020).…”
Section: Caregivers' and Children's Musical Behaviors During Social Dsupporting
confidence: 92%
See 1 more Smart Citation
“…Results showed that caregivers tended to engage more frequently in music-related activities (e.g., listening to music) during social distancing compared with a typical day before social restrictions. This finding agrees with a general trend revealed by studies showing an increase in the time adults spent on musical activities during the COVID-19 pandemic (Cabedo-Mas et al, 2020;Krause et al, 2020).…”
Section: Caregivers' and Children's Musical Behaviors During Social Dsupporting
confidence: 92%
“…It has been shown that social interactions through music can effectively reduce feelings of loneliness and provide a sense of togetherness and belonging (Labbé et al, 2007;Laukka, 2007;Miranda and Claes, 2009;Tymoszuk et al, 2020). This may explain a general trend observed across the globe regarding the use of music through online musical gatherings (e.g., live music streams and concerts) as a positive coping strategy to deal with feelings of loneliness and social/physical disconnection (Cabedo-Mas et al, 2020;MacDonald et al, 2020;Vandenberg et al, 2021).…”
Section: Caregivers' and Children's Musical Behaviors During Social Dmentioning
confidence: 99%
“…reading and listening to the radio/music) was associated with lower levels of depressive and anxiety symptoms and higher levels of life satisfaction in adults in the UK [5]. Similarly, musical activities helped improve people's mood, boosted their confidence and sense of positivity, and led to a greater sense of connectedness in adults in Spain [6]. It has been proposed that people used the arts to help cope with their emotions and improve their self-development during lockdown [2].…”
Section: Introductionmentioning
confidence: 95%
“…For those who have experienced an increased negative mood as a result of the pandemic, music listening has helped them to cope emotionally, and regardless of changes in emotions, music has provided a sense of social connectedness for all (Fink et al, 2021). Similar coping effects of music listening have been reported related to relaxation, raising mood, escapism, and social surrogacy, as well as an increased perception of the general value of musicfor wellbeing during lockdown (Cabedo-Mas et al, 2021). In close relation to our research, a study conducted by Yu-Cheong Yeung (2020) has demonstrated the existence of a link between the COVID-19 pandemic and an increase in listening to music deemed nostalgic on the music streaming service Spotify.…”
Section: Introductionmentioning
confidence: 82%